Heterozygote and Mutation Detection by Direct Automated Fluorescent DNA Sequencing Using a Mutant Taq DNA Polymerase - R.B. Chadwick; M.P. Conrad; M.D. McGinnis; L. Johnston-Dow; S.L. Spurgeon; M.N. Kronick (BioTechniques)
We describe a method for direct cycle sequencing of PCR fragments amplified from genomic DNA or cDNA. DNA sequencing template is amplified using PCR and oligonucleotide primers flanking the region of interest. The amplified fragment is directly cycle sequenced using fluorescent sequencing primers, Sanger dideoxy sequencing chemistry and an enzyme mixture of a mutant Taq DNA polymerase and thermostable pyrophosphatase. The sequence ladders produced are analyzed on a real-time, automated four-color sequencing system. The methodproduces sequence ladders from unpurified PCR fragments of sufficiently high quality such that heterozygotes can be reproducibly detected and identified by sojhare that recognizes signal-strength patterns indicative of mixed-base positions.